Community readiness and acceptance for the implementation of the malaria vaccine among caretakers of at-risk children in sub-Saharan Africa: a systematic review and meta-analysis - Eustes Kigongo; Sean Steven Puleh; Amir Kabunga; Stella Immaculate Akech; Francis Ocen; Marc Sam Opollo; Moses Ebong (Malaria Journal)
Abstract Background Malaria remains a leading cause of morbidity and mortality in sub-Saharan Africa, particularly among children under five. The introduction of the malaria vaccine presents an opportunity to reduce malaria-related deaths. However, the success of vaccination campaigns depends on community acceptance and willingness to vaccinate. This study aimed to assess the pooled acceptance and willingness to adopt the malaria vaccine in sub-Saharan Africa, with a focus on variations across regions and the impact of the COVID-19 pandemic. Methods A systematic review and meta-analysis were conducted following PRISMA guidelines. A comprehensive search of databases, including PubMed, ScienceDirect, Google Scholar, and African Journals Online, was performed. Studies reporting on malaria vaccine acceptance and willingness among caregivers of children under five in sub-Saharan Africa were included. Data were extracted and analysed using STATA, with heterogeneity assessed through the I2 statistic. Subgroup analyses were performed based on region and pre- and post-COVID periods. Publication bias was assessed using Egger’s test. Results A total of 1611 records were identified, and 34 studies met inclusion criteria after screening. Of these, 25 studies with a combined sample of 25,867 participants were included in the meta-analysis. The pooled acceptance rate for the malaria vaccine among caregivers of children under five in sub-Saharan Africa was 82% (95% CI: 73%–90%), while the pooled willingness rate was 80% (95% CI: 70%–90%). Subgroup analyses showed no statistically significant differences in acceptance or willingness by COVID-19 period or region, though the lowest acceptance (53%) was reported in the DRC. High heterogeneity was observed (I2 > 99%), and publication bias was indicated in the willingness outcome (Egger’s test, P = 0.002). Conclusion The findings indicate high levels of acceptance and willingness among caregivers to vaccinate children under five against malaria in sub-Saharan Africa, suggesting strong community readiness for vaccine rollout. However, the observed heterogeneity and potential publication bias highlight the need for context-specific strategies and further high-quality studies to support implementation and uptake across diverse regions. Systematic review registration The protocol has been registered with PROSPERO registration number: CRD42023480528